PRODUCTIVE WAKAF AS A STRATEGY TO SUPPORT THE ECONOMY OF THE PEOPLE - Jumadiah; Hamdani; Sutriani; Nurdan; Mustika Amri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Waqf is one of the economic instruments of the people that can be used for the economic empowerment of the people. Basically, waqf is productive in the sense that it must produce because waqf can fulfill its purpose if it has produced where the results are used according to its intended purpose (mauquf alaih). This research was conducted using a descriptive method with a qualitative approach based on data sources from literature studies and observations. The purpose of this study is to provide information related to waqf management. The results of the study show that the implementation of productive waqf to improve Islamic economic welfare can be carried out with various applications with development design models, including establishing mosques (places of worship), business shops, gas stations or gas stations, banking, offices, multi-purpose halls, photocopying, apartments or boarding houses, hotels, and others so as to achieve general benefits as a benefit for the people with social, economic, and cultural development of the community.